FACTORS OF SOCIO-PSYCHOLOGICAL ADAPTATION AND ANXIETY OF REFUGEES DURING THE WAR - Harkusha Inesa; Dubinskyi Serhii (Alfred Nobel University Publisher, 2023)
The article provides a theoretical analysis of the problem of anxiety, the tendency of a person to experience anxiety, which is connected with the premonition of real or imagined danger. The purpose of the article is to review and analyse the factors of socio-psychological adaptation and anxiety of refugees in terms of war, as well as psychological techniques to develop in them a new attitude to stress reactions as a resource that can strengthen immunity to traumatization. The study used the methods of terminological, substantive and statistical analysis in determining the content and essence of anxiety as a state and process of experiencing, as well as modelling and projecting methods to find factors of social and psychological adaptation and reducing the level of anxiety of refugees during the war. It has been emphasized that anxiety is an individual psychological feature reflecting an increased tendency to feel alarm in various life situations, in particular those that do not objectively foresee this. Common and distinctive features between anxiety and alarm have been identified. In the structure of anxiety, cognitive, emotional and operational components have been found and described, among which the dominant position is occupied by an emotional response to an unfavourable life situation. It has been shown that anxiety is divided into two main categories: covert and overt. It has been pointed out that there is a connection between the state of alarm and the strength of the individual's nervous system. Assumptions are expressed regarding the inverse correlation of the strength and sensitivity of the subject's nervous system. The analysis of scientific research has shown that anxiety enables an individual to respond to a threatening situation adaptively. Anxiety also changes the nature of the behaviour, leads to increased behavioural activity, encourages more intense and purposeful efforts, and thereby performs an adaptive function. It has been emphasized that if the anxiety is intense and long-lasting, it prevents the formation of adaptive behaviour and leads to violations of behavioural integration, and sometimes to clinically expressed disorders of the psyche and behaviour. Peculiarities of the person's psychological states in terms of war events have been analysed. It is argued that the most important self-preservation strategy is to change the subject's attitude to war traumatization. A person should know that it is not at all necessary to become a victim of life's trials, that not every stress causes post-traumatic disorders, and that stress energy can be transformed and used effectively. It has been established that a new attitude to stress reactions as a resource strengthens immunity to trauma and promotes post-traumatic growth. It has been noted that adaptation and the ability to adapt is a prerequisite for the future active and productive activity of an individual in any sphere of life. When a person feels free and comfortable (adapted), they perform both their social and professional roles well, which is very important in the process of social interaction both during education and in later life. Adaptation is divided into external and internal, and such types of adaptation are distinguished as pedagogical, professional, social, biological, and psychological ones. Factors have been clarified, and external and internal criteria of psychological and pedagogical adaptation have been distinguished. At the same time, it has been concluded that socio-psychological adaptation to the conditions of a military conflict occurs as an adaptation to a socially tense, constantly changing environment. Therefore, it is important to shift the emphasis from the state of adaptation to the properties of adaptability of the individual and the community, which are associated with such constructs as resilience, psychological resilience, and group efficiency.